Diabetic Retinopathy: Are lncRNAs New Molecular Players and Targets? - Simona Cataldi; Mariagiovanna Tramontano; Valerio Costa; Marianna Aprile; Alfredo Ciccodicola (Antioxidants, 2022)
The growing incidence of diabetes mellitus worldwide implies the increasing prevalence of several related macro- (e.g., hypertension and atherosclerosis) and micro-vascular (e.g., nephropathy and retinopathy) complications. Notably, diabetic retinopathy (DR) is the leading cause of blindness in older diabetic patients and can occur with different degrees of severity. Chronic hyperglycemia is the main determinant of the functional damage of retinal cells. The oxidative stress, inflammatory factors and vascular endothelial growth factor signaling have been widely reported as contributors of DR onset and progression, and an emerging role has been described for different classes of non-coding RNA, including several long non-coding RNAs (lncRNAs). Here, we report the main results of all research articles (i.e., 150) listed on PubMed database from 2014 to 2022 regarding the putative role of lncRNAs in DR, including small nucleolar RNA host genes (SNHGs). Particularly, in this review we describe all lncRNAs and SNHGs with altered expression in DR and related contexts, discussing their association with DR outcomes, their mechanism of action related to DR, the molecular/functional effects, as well as the biological and experimental contexts. Thus, herein we provide an overview of the current state of knowledge regarding the putative involvement of 50 lncRNAs and SNHGs in the pathogenesis of DR, highlighting their potential as therapeutic targets or biomarkers for improving the clinical management of DR.